Building the competences of an accounting specialist: requirements and challenges - Kazlauskaitė, Agnė (Buhalterinės apskaitos teorija ir praktika, 2024)
Accounting specialists play an essential role in ensuring the company's financial stability and legality, so their level of competence directly affects the efficiency and success of the company's operations. In this labor market, accounting specialists must have mastered not only technical knowledge, such as preparation of financial reports and tax calculations, but also be familiar with the latest technologies and information systems. Analytical skills, problem-solving ability, and adherence to ethical behavior are also emphasized. The challenges in the labor market are the continuous improvement of technology, so accounting specialists must adapt to automation processes and be able to effectively use new digital tools. In addition, as the legal environment changes and regulations become more stringent, it is necessary to constantly update knowledge. In this context, continuous training and professional development become especially important in order to ensure a high level of professionalism. This work analyzes how accounting specialists can shape their competence in a way that meets the needs of today's market, what requirements are placed on them, and what challenges they face in order to remain competitive and professional in their field. The purpose of the study was to determine the most important competencies and requirements, problems, and challenges of accounting specialists. Research methods: the analysis of scientific literature used for the work, the method of analyzing job advertisements, expert interviews, information comparison, systematization, and summarization.
Keywords: competencies; accounting specialist; job announcements; requirement for accountant